VIBRATION EXPERIMENT OF COAL SHEARER CUTTING UNIT GEARBOX HOUSING IN OBLIQUE CUTTING - LI Peng (Jixie qiangdu)
Oblique cutting is a working condition in fully mechanized mining whose main task is making it possible for long wall shearer to cut the coal seam,and it is a harsh working condition since the shearer is forced to be bent. In this study,dynamic characteristics in oblique cutting for the long wall shearer cutting unit gearbox（ SCUG） are investigated experimentally based on National Coal Mining Equipment Laboratory of China. Real oblique cutting process in coal mining is reproduced in this experiment and vibration acceleration data is obtained. The vibration data is analyzed in time domain,frequency domain and timefrequency domain for investigating the rules of dynamic characteristics for SCUG. Beat vibration phenomenon and the coupling of gear mesh frequencies are found in experiment,and they may cause local resonance and reduce fatigue life of SCUG. The impact of cutting load on beat phenomenon and frequency coupling is investigated,and some conclusions related to the impact of cutting load on dynamic characteristics of nonlinear gear system are obtained.